Antibacterial efficacy of mesenchymal stem cell administration in diabetic rats infected with MRSA: An experimental study - Kabalcı, Mehmet; Şahin, Mustafa; Zengin, Mehmet; Savcı, Ünsal; Çifci, Aydın (Journal of Surgery and Medicine, 2019)
Aim: The antibacterial effects of mesenchymal stem cell (MSC) administration and vancomycin, tigecycline and daptomycin treatment were compared in a diabetic rat model with wound infection due to methicillin-resistant Staphylococcus aureus (MRSA). Methods: Experiment, negative and positive control groups were created using 60 rats. The antibacterial efficacy of MSC, vancomycin, tigecycline and daptomycin were compared. All rats had diabetes induced with streptozotocin. They were shown to be hyperglycemic with fasting blood glucose monitoring. During surgery, subdermal pouches were created. Group 0 (negative control group) was not infected or treated. All other groups were infected with MRSA. Group 1 (positive control group) was infected but not treated. The other 4 groups were determined as treatment groups: Group MSC was treated with MSC, Group Van treated with vancomycin, Group Tig treated with tigecycline and Group Dap treated with daptomycin. After one week of treatment, samples were collected following euthanasia. Tissue samples were evaluated after histopathologic staining with hematoxylin/eosin. The presence of MSC in the wound region was shown by immunofluorescent staining. Bacterial colony counts were identified quantitatively. TNF-α, TGF-β, IL-1, PDGF, FGF, VEGF and Caspase-3 levels in blood samples were measured with the ELISA method. Results: While bacterial colonization was not observed in Group 0, a clear colonization was identified in Group 1. Full eradication was achieved in Group Tig and Group Dap. Eradication could not be achieved for 1 rat in Group Van and 4 rats in Group MSC. The uncontaminated negative control group rats (Group 0) had minimal inflammation, while the most severe inflammation was observed in infected and untreated rats (Group 1) (P<0.001). Group-MSC, Group-Van, Group-Dap and Group-Tig had moderate levels of inflammation and edema. The MSC group showed significant increase in vascularity (P=0.001). Adhesion and fibrosis were observed significantly less in the negative control group and MSC groups, similarly (P<0.001, P<0.001). Conclusion: MSC may exert antibacterial-like effects for MRSA-induced wound infection treatment in diabetic rats, and limit the inflammation in and around the wound. Further clinical studies researching the synergistic effects of MSC with antibiotherapy for treatment of diabetic wound infections are needed.